PENINGKATAN HIGHER ORDER THINKING SKILLS (HOTS) MAHASISWA DENGAN MENGGUNAKAN MODEL SELF DIRECTED LEARNING (SDL) PADA MATA KULIAH PENGEMBANGAN PROFESI GURU - Muskitta, Marike (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: This research aims to improve students Higher Order Thinking Skills by using the SelfDirected Learning Models (SDL).Methods: This research uses an exploratory research model. Qualitative data was obtained throughinterviews and questionnaires. Quantitative data was obtained through pretest and posttest data. Theresearch subjects were Biology students at FKIP Pattimura University which offered teacherprofessional development courses. The research instrument used was a test. Quantitative dataanalysis uses descriptive statistics and test scores, while qualitative data analysis uses data collectionprocedures, data reduction, data presentation, and building a conclusion.Results: The results of calculating the implementation of the Self Directed Learning models (SDL) toimprove students higher order thinking skills in teacher professional development courses show anaverage value of 97.36 with a significant value of 0.000 which is smaller than 0.05 (0.000<0.05) sothat the hypothesis can be accepted.Conclusion: The application of the Self Directed Learning models (SDL) is very effective in improvingthe higher order thinking skills of prospective biology teacher students.